Insights into the effects of different drying methods on protein oxidation and degradation characteristics of golden pompano (Trachinotus ovatus) - Chen, Peng; Qiu, Yingjie; Chen, Shengjun; Zhao, Yongqiang; Wu, Yanyan; Wang, Yueqi (Frontiers in Nutrition, 2022)
The quality of dried fish products differs based on the drying method employed owing to the different drying principles, with changes in protein affecting the quality of these products. Therefore, we investigated the differences in golden pompano (Trachinotus ovatus) fish tissue structure and protein physicochemical properties under different drying methods. Freeze drying (FD) induced less tissue damage, leaving more intact myofibrils, than that of hot air drying (HAD) and heat pump drying (HPD). The structural stability of myofibrillar protein was retained to a greater extent after FD, while myoglobin oxidation was lower, and fish meat color was well maintained. Our findings not only elucidated the effects of several drying methods on the physicochemical properties of fish protein, but also determined the mechanism underlying quality changes observed during the drying process. This provides a theoretical reference for the study of dried fish filet processing.